Wu Wenying and the Art of Southern Song Ci Poetry - Fong, Grace S., 1948- (Book collections on Project MUSE., 1987)
The author begins with a biography exploring the moral and aesthetic implications of Wu's life as a guest-poet" patronized by officials and aristocrats, and continues with a reconstruction of the historical and literary context needed for modern readers to grasp his poetic techniques. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905